Court-Mandated Patients’ Perspectives on the Psychotherapist’s Dual Loyalty Conflict – Between Ally and Enemy - Merkt, Helene; Wangmo, Tenzin; Pageau, Félix; Liebrenz, Michael; Devaud Cornaz, Corinne; Elger, Bernice (Frontiers in Psychology, 2021)
Background: Mental health professionals working in correctional contexts engage a double role to care and control. This dual loyalty conflict has repeatedly been criticized to impede the development of a high-quality alliance. As therapeutic alliance is a robust predictor of outcome measures of psychotherapy, it is essential to investigate the effects of this ethical dilemma. Methods: This qualitative interview study investigates patients’ perceptions of their therapists’ dual role conflict in court-mandated treatment settings. We interviewed 41 older offenders using a semi-structured interview guide, the interviews were subsequently analyzed following thematic analysis. Results: We first present the patients’ perceptions of their treating psychotherapist’s dual loyalty conflict, which was linked to their overall treatment experience. In a second step, we outline the study participants’ reasons for this judgement, which were most commonly linked to feelings of trust or betrayal. More specifically, they named certain therapist characteristics and activities that enabled them to develop a trustful therapeutic alliance, which we grouped into four topics: 1) Respecting the patient’s pace and perceived coercion; 2) Patient health needs to be first priority; 3) Clarity in roles and responsibilities; and 4) The art of communication – between transparency and unchecked information sharing. Discussion: Developing a high quality alliance in mandatory offender treatment is central due to its relationship with recovery and desistance. Our findings show that some therapists’ characteristics and activities attenuate the negative impact of their double role on the development and maintenance of the alliance. To increase the effectiveness of court-mandated treatments, we need to support clinicians in dealing with their dual role to allow the formation of a high quality therapeutic alliance. Our qualitative interview study contributed to this much-needed empirical research on therapist’ characteristics promoting a trustful relationship in correctional settings.